Planning a Wildland-Urban Interface Communication Program - Martha C. Monroe (EDIS)
Revised! FOR-197, a 3-page illustrated fact sheet by Martha C. Monroe, provides guidelines for planning a communication effort based on the U.S. Fish and Wildlife Service’s National Outreach Strategy. Includes references. Published by the UF School of Forest Resources and Conservation, July 2008.